Physiological responses of Lemna minor to polystyrene and polymethyl methacrylate microplastics - Karla Košpić; Sandra Vitko; Luka Kobelščak; Ana Matešković; Petra Peharec Štefanić; Nino Dimitrov; Mirta Tkalec; Biljana Balen (Current Plant Biology)
Due to its economic viability, plastic has become an indispensable material whose mass production continues to increase, raising concerns about its impact on living organisms. Its long persistence in the environment and slow degradation to microplastics (MPs) pose a serious problem, as MPs can penetrate plants and animals and interfere with physiological processes. In this study, the in vitro cultured duckweed Lemna minor was exposed to 10, 50 and 100 mg L−1 polystyrene (PS) and polymethyl methacrylate (PMMA) MPs for 7 days to investigate uptake and effects on growth, photosynthetic performance and oxidative stress parameters. We hypothesized that PS-MPs and PMMA-MPs would have different uptake patterns and effects on the physiology of L. minor, due to their different properties. A pronounced agglomeration of PMMA-MPs in the exposure medium correlated with a lower uptake of PMMA-MPs compared to PS-MPs. However, PMMA-MPs induced severe ultrastructural changes in the chloroplasts and a decrease in chlorophyll a and b content, resulting in reduced plant growth. In contrast, treatments with PS-MPs stimulated growth, especially frond area, probably as a result of increased content of photosynthetic pigments and improved photosynthetic efficiency. Both MP types induced mild oxidative stress, which triggered protective responses, but the activation of antioxidant defense was dependent on the polymer type, as PMMA-MPs slightly increased proline content and superoxide dismutase activity, while PS-MPs induced peroxidase activities. In conclusion, PS-MPs seem to be less harmful as they promote growth and photosynthetic efficiency, whereas PMMA-MPs have negative effects on L. minor physiology by causing structural damage to subcellular parts and inhibiting their function.